Transcriptomic profiling and validation of early onset estrogen receptor-positive breast cancer patients - Siddig, Alaa Abdelaziz Mahmoud (2023)
Early-onset breast cancer (≤45 years) is an area of debate due to the adverse clinicopathological features and the unfavourable clinical outcomes observed in earlyonset patients compared to late-onset patients (> 45 years). The present study compared the clinicopathological features of early and late-onset breast cancer patients diagnosed at Hospital Universiti Sains Malaysia during the period 2013 – 2022 (n=570). Consequently, the transcriptomic profile of Estrogen Receptor (ER)- positive breast cancer was compared between early and late-onset patients using the Clariom S gene chip from Affymetrix (n=14), validation in larger sample size conducted using in silico analysis and real-time polymerase chain reaction (RT-qPCR). The Kaplan- Meier plot used to assess the prognostic significance of the genes that exhibit differential expression between early and late-onset breast cancer tissues. Immunohistochemical analysis utilized to assess the protein expression level of RANBP3L and GLYATL-1; genes encoded by the differentially expressed genes. Finally, the distribution of the tumour stroma ratio and the tumour infiltrating lymphocytes were compared between early and late-onset ER-positive breast cancer haematoxylin and eosin-stained tissue sections. Results showed that early-onset breast cancer tend to have large size (> 5cm) (28.3% vs 13.5%), and a higher proportion of luminal B subtype (22.8% vs 14.2%). The bilateral breast cancer incidence is higher in early than in late-onset patients (9.4% vs 3.6%). The transcriptomic profile of ERpositive early-onset breast cancer differentially expressed 11 genes (fold change < 3 or >3; adjusted p-value <0.05). Six genes out of eleven have validated expression. Enrichment analysis revealed that differentially expressed genes between early and late-onset ER-positive breast cancer with unadjusted p-value < 0.01 implicated in pathways related to focal adhesion, axon guidance and complement and coagulation cascades (FDR p-value <0.05). Survival analysis showed that loss of expression of SFXN2, GLYATL-1, RANBP3L and ESR-1 which is characteristic of the transcriptomic profile of early-onset ER-positive breast cancer was significantly associated with shorter relapse-free survival. IHC analysis showed that the expression of GLYATL-1 and RANBP3L proteins exhibit an association with lymph node positivity and low histopathological grade (P<0.005 and 0.038) respectively. A low tumour stroma ratio was significantly associated with ER-positive breast cancer patients with age (50-59 years). The collected evidence indicates that the early onset of breast cancer (≤45 years) exhibits adverse clinicopathological features compared to the late onset of breast cancer (>45 years). The transcriptomic profile of the early-onset ER-positive breast cancer differentially expressed genes that are implicated in cancer progression and metastasis. Breast cancer developed in old age is characterized by a low tumour stromal ratio which may predict a good prognosis.